Optical solitons for the dispersive concatenation model with spatio-temporal dispersion having multiplicative white noise - Arnous, Ahmed H.; Elsherbeny, Ahmed M.; Secer, Aydin; Ozisik, Muslum; Bayram, Mustafa; Shah, Nehad Ali; Chung, Jae Dong (ELSEVIER, 2024)
This investigation of the current work presents the dispersive concatenation model that integrates the spatiotemporal dispersion and the effect of multiplicative white noise in the Ito sense. The study aims to secure stochastic optical soliton solutions within this framework. To achieve this purpose, we implemented the enhanced Kudryashov technique and the new projective Riccati equations strategy. Initially, the traveling wave transform hypothesis was applied to convert the stochastic model into its nonlinear ordinary differential equation form, encompassing real and imaginary components with emerging the related parametric restrictions. Subsequently, we introduced the enhanced Kudryashov and the new projective Riccati equations techniques successfully employed in analyzing the generated nonlinear ordinary differential equation. By utilizing the appropriate solution sets, which encompass variables with unknown values and necessary transformations, we have derived many stochastic optical soliton-type solutions for the model. Detailed discussions for the dynamics of some selected soliton solutions are presented with the supporting of the 3D and 2D graphs that illustrate the white noise effect on these solitons.
Keywords: Wiener process; Stochastic; Optical solitons; Riccati; Concatenation; Dispersive; PERTURBATION; Materials Science; Physics